2015
DOI: 10.4236/health.2015.711162
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Smoking: A Literature Overview

Abstract: The purpose of this review is to summarize the more recent research findings regarding the relationship between exercise and smoking behavior. Reviewed studies have been presented according to themes and research design types. Initially cross-sectional and longitudinal epidemiological studies have been reviewed in order to map findings regarding the correlations between those two behaviors. Moreover, studies exploring variables that function as mediators or moderators between smoking and exercise relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 89 publications
2
16
0
2
Order By: Relevance
“…These findings are partly in agreement with Bakrania et al (2016) that demonstrated lower prevalence rates of smoking among the “Sedentary exercisers” but higher ones for the “Busy bees” and the “Light movers”; but these results were not adjusted for potential confounders. Overall, PA has been negatively associated with smoking Hassandra et al (2015) . The “Sedentary exercisers” and “Busy bees” were also negatively associated with obesity whereas no association was found for the “Light movers”, a finding in agreement with other studies ( Bakrania et al, 2016 ; Loprinzi et al, 2014 ; Cristi-Montero et al, 2017 ) but not with another one ( Sugiyama et al, 2008 ) showing also lower prevalence rates of obesity among the “Light movers”.…”
Section: Discussionmentioning
confidence: 94%
“…These findings are partly in agreement with Bakrania et al (2016) that demonstrated lower prevalence rates of smoking among the “Sedentary exercisers” but higher ones for the “Busy bees” and the “Light movers”; but these results were not adjusted for potential confounders. Overall, PA has been negatively associated with smoking Hassandra et al (2015) . The “Sedentary exercisers” and “Busy bees” were also negatively associated with obesity whereas no association was found for the “Light movers”, a finding in agreement with other studies ( Bakrania et al, 2016 ; Loprinzi et al, 2014 ; Cristi-Montero et al, 2017 ) but not with another one ( Sugiyama et al, 2008 ) showing also lower prevalence rates of obesity among the “Light movers”.…”
Section: Discussionmentioning
confidence: 94%
“…Panels B and D describe the time-course of the responsiveness over the six 5-min within-session intervals (no inferential statistics were computed on these data). The split-plot ANOVA resulted in a strong significant housing-by-drug interaction ( ²p = .15, F (1,32) = 5.75, p = .02) along with a negligible non-significant housing-by-drug-by-sex interaction ( ²p = .01, F (1,32) = 0.36, p = .55). Importantly, planned crossed contrasts indicated that the attenuating effect of prenatal exercise was significant and strong in females (d = 0.75, t (32) = 2.11 at p = .02), but modest and non-significant in males (d = 0.34, t (32) = 0.96 at p = .17).…”
Section: Prenatal Wheel-running Activitymentioning
confidence: 98%
“…It was also found that exercisers can limit and stop smoking more easily than non-exercisers (Godin, 1989;Boudreaux, Francis, Taylor, Scarinci, & Brantley, 2003;Hassandra et al, 2015). Exercise is now recognized as a low cost factor of prevention and smoking cessation and can be used both for smoking prevention and for smoking cessation.…”
Section: Introductionmentioning
confidence: 99%
“…Several intervention programs based on psychological support, focused on certain factors, such as motivation, self-efficacy and social support relations, since they appear to affect the smoking cessation attempt (Johnston, Johnston, Pollard, Kinmonth, & Mant, 2004;Norman, Conner, & Bell, 1999;Hassandra, Goudas, & Theodorakis, 2015), and also because the need for emotional coverage appears to be a very important reason for smoking (Singleton & Pope, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation